2017
DOI: 10.1007/s40799-017-0183-4
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation of Shot Peening on Case Hardened SS2506 Gear Steel

Abstract: Shot peening is a manufacturing process commonly used to increase fatigue life in components for the automotive and aircraft industry. In this paper the effect of shot peening is described for a case hardened gear steel. For gears there are three main factors from shot peening that influence fatigue life: residual stresses, microstructure and surface roughness. The paper describes an experimental series where these parameters were measured for common industrial shot peening settings. The aim was to show how se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(7 citation statements)
references
References 30 publications
1
6
0
Order By: Relevance
“…5, the surface roughness Ra of SP5 is about 21.28% less than that of SP1, whereas the reduction is about 7.15% for Rz. It is revealed that proper increase of coverage can reduce the surface roughness of gear tooth flanks, and the results are compatible with that of other literature [10,17,34,39].…”
Section: Surface Roughnesssupporting
confidence: 90%
See 1 more Smart Citation
“…5, the surface roughness Ra of SP5 is about 21.28% less than that of SP1, whereas the reduction is about 7.15% for Rz. It is revealed that proper increase of coverage can reduce the surface roughness of gear tooth flanks, and the results are compatible with that of other literature [10,17,34,39].…”
Section: Surface Roughnesssupporting
confidence: 90%
“…The maximum compressive residual stress for coverage levels less than 1000% exhibits obvious growth tendency with coverage. Beyond the coverage of 1000%, there are no significant variations in the magnitude of maximum compressive residual stress, indicating that compressive residual stress has a saturation value [34]. AGMA [14] reported the maximum residual compressive stress was about 50%-60% of the ultimate tensile strength (UTS) of the peened gear surface.…”
Section: Residual Stressmentioning
confidence: 99%
“…A large number of experimental investigations were carried out to study this surface treatment process. These investigations focused on adjusting its influential parameters in order to control its detrimental effects and simultaneously to enhance the beneficial effects arising from the induced compressive residual stresses in a shot peened component [5] [6] [7] [8] [9] [10] [11] [12]. Moreover, this approach was also used to develop empirical models of induced residual stress in terms of process parameters [13] [14].…”
Section: Introductionmentioning
confidence: 99%
“…Taking into account the thermal influence of the welding process, fatigue-weak areas exist, especially in the fusion zone (FZ) and heat affected zone (HAZ) of welded structures [4]. One of the ways of improving the strength properties in these zones is the surface strengthening treatment after welding, such as shot peening (SP) [5,6], laser shock peening (LSP) [7], ultrasonic peening [8], water jet peening (WJP) [9] and fine particle peening technology [10]. During the SP process, the surface is bombarded by small spherical balls.…”
Section: Introductionmentioning
confidence: 99%